(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Central African Republic (CAR) is one of the most war-affected countries in the world. The number of forcibly displaced people has grown significantly along with the emergence of many infectious and non-infectious diseases in this region. Very little information is available regarding the health of internally displaced persons (IDPs) of this country. Objectives: To find out the prevalence of common diseases among IDPs of a selected region of CAR. Materials and Methods: This descriptive cross-sectional study was conducted at a United Nations level-II hospital, run by Bangladesh medical contingent from November 2017 to October 2018. Patients of both sex irrespective of age who attended at least once to the medical outpatient department of the hospital included in the study. Results: Out of 1561 respondents 57% were female with a female to male ratio1.3:1. Among the health problems identified, communicable diseases were 65.59% and non-communicable diseases 34.40%. Malaria (21.19%), diarrhoeal disease (17.86%) respiratory tract infection (15.52%) and HIV/AIDS (9.96%) were the most common communicable diseases. Non-communicable diseases mainly affected the adult population where the prevalent diseases were hypertension 18.99% followed by diabetes mellitus 15.08%, severe malnutrition 11.91% and mental and post-traumatic stress disorder (PTSD) 08.93%. Conclusion: Limited provisions on healthcare facilities imposes a huge health risk for the IDPs especially, easily preventable communicable diseases. An integrated effort from local and international bodies is required for the restoration of the basic health services to continued provision of medicines, medical appliance and provide community health education and thereby, improve the overall health status of this region. JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 181-185